The Effectiveness of Collecting PBB in The Urban-Rural and BPHTB Sectors for Increasing PAD in Malinau Regency - Ester; Milwan; Riswanda (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2022)
The role of local regional government becomes very important to regulate and manage. development in the region in self uses the Regional Original Income (PAD) owned by each region. One source of local revenue comes from the Rural and Urban Land and Building Tax (PBB P2) and the land and Building Rights Acquisition Fee (BPHTB). This study aims to determine the effectiveness of PBB and BPHTB collection in Malinau Regency, and the contribution of revenue PBB and BPHTB on PAD of Malinau Regency. The theory used by Devaas, a989:62 The Research method used is descriptive qualitative. The data collection method used is documentation, observational interviews and literature study. The selected informants are people related to tax collection, both at the BPKD Malinau Regency and ordinary people. The data used in this study in the target and realization in PBB and BPHTB revenues in 2017–2021. The results of the study indicate that the level of effective people of collecting PBB P2 and BPHTB from 2017 to 2021 is said to be very ineffective. Where the highest effectiveness occurs in 2021 with percentages of 78.66% and 447,57 %, respectively. According to the level of effectiveness of PBB and BPHTB receipts, Malinau Regency has not been effective in the las 5 years. Meanwhile, the contribution level of PBB P2 and BPHTB revenues to Malinau Regency's PAD is classified as less in the last 5 years.